Pengaruh Menginang Terhadap Tingkat Keparahan Jaringan Periodontal Pada Lansia Di Desa Tugu Kecamatan Jumantono Kab. Karanganyar Tahun 2016 - Shinta Graharani, Afrinda, Dwi Kurniawati, SKG. MPH, drg. Fitria Nur Malita Sari (2016)
Periodontal tissues disease can cause by two factors, that is local factor and systemic factor. Local and systemic factors can be aggravated by predisposed factor, as chewing betel. Chewing betel was tradition which evolved in Indonesia by chewing mixture ingredients like betel leaf, areca nut, tobacco, gambir and lime. This study aimed was to know the influence of chewing betel to the severity of elderly's periodontal tissue in Desa Tugu Kecamatan Jumantono Kabupaten Karanganyar year 2016. The method of research that used was analytic observasional then for samples as much as 50 elderly selected using Total Sampling and based on restriction criteria. The researches was interview about their chewing betel habbit then examined using PDI (Periodontal Disease Index) to know the severity of periodontal tissues. The result of this research was chewing betel influence the severity of periodontal tissues. The duration of chewing betel has significant influence (p = 0.000 (p<0.05)) to the severity of elderly's periodontal tissue. The duration of chewing betel has significant influence (p = 0.000 (p<0.05)) to the severity of elderly's periodontal tissue too. Chi Square's test result showed duration, frequency of chewing betel and PDI was significant (p= 0.003 (p<0.05)), it can concluded that duration, frequency of chewing betel had an influence to the severity of elderly's periodontal tissue.